A Study on Fundamental Analysis of Top 10 Gainers on BSE (Last Fiscal Year 2023-24) - Deshmukh, Vishal; Kamble, Rahul (International Journal of Engineering and Management Research, 2025)
This study aims to evaluate the financial health and investment potential of the top 10 gainers listed on the Bombay Stock Exchange (BSE) for the fiscal year 2023–2024 through fundamental analysis. Using secondary data from company financial statements, BSE reports, and public disclosures, key metrics such as EPS, P/E ratio, ROE, and debt-equity ratios are analyzed. The results provide insights into whether the stock price growth of these companies is supported by solid fundamentals or driven by market speculation. The paper concludes with sector-specific recommendations for value and growth investors.